High frequency targeted mutagenesis in Arabidopsis thaliana using zinc finger nucleases - Zhang, Feng (National Academy of Sciences, 2010)
We report here an efficient method for targeted mutagenesis of Arabidopsis genes through regulated expression of zinc finger nucleases (ZFNs)—enzymes engineered to create DNA double-strand breaks at specific target loci. ZFNs recognizing the Arabidopsis ADH1 and TT4 genes were made by Oligomerized Pool ENgineering (OPEN)—a publicly available, selection-based platform that yields high quality zinc finger arrays. The ADH1 and TT4 ZFNs were placed under control of an estrogen-inducible promoter and introduced into Arabidopsis plants by floral-dip transformation. Primary transgenic Arabidopsis seedlings induced to express the ADH1 or TT4 ZFNs exhibited somatic mutation frequencies of 7% or 16%, respectively. The induced mutations were typically insertions or deletions (1–142 bp) that were localized at the ZFN cleavage site and likely derived from imprecise repair of chromosome breaks by nonhomologous end-joining. Mutations were transmitted to the next generation for 69% of primary transgenics expressing the ADH1 ZFNs and 33% of transgenics expressing the TT4 ZFNs. Furthermore, ≈20% of the mutant-producing plants were homozygous for mutations at ADH1 or TT4, indicating that both alleles were disrupted. ADH1 and TT4 were chosen as targets for this study because of their selectable or screenable phenotypes (adh1, allyl alcohol resistance; tt4, lack of anthocyanins in the seed coat). However, the high frequency of observed ZFN-induced mutagenesis suggests that targeted mutations can readily be recovered by simply screening progeny of primary transgenic plants by PCR and DNA sequencing. Taken together, our results suggest that it should now be possible to obtain mutations in any Arabidopsis target gene regardless of its mutant phenotype.